God and Religion in the Postmodern World: By David R. Griffin (series title "Essays in Postmodern Theology"). Albany, NY: SUNY Press, 1989, 175pp. (American Journal of Islam and Society, 1991)
Griffin's larger program in God and Religion in the Postmodern Worldis to develop a process theology able to meet the challenges and opportunitiespresented by science and modernity. This process theology draws extensivelyon the work of Whitehead and Hartshorne and essentially entails destroyingmodernity as an ideology while retaining certain parts of the scientificworldview, returning to some aspects of premodernity (such as the view ofenchanted nature), and creating a holistic, pluralistic, dynamic view of thenature of God and humanity.Besides this program, Griffin develops a number of insightful ideas.Getting around the problem of describing a phenomenon like postmodernism,which wants to preclude all closure and definition, Griffin makes the casethat destructive postmodemism is really ultramodernism, modernism carriedto its logical conclusion. This avoids the confusion of "constructive" postmodernthought.Griffin also makes the case for panentheism, as opposed to pantheismor the absolute dichotomy popular two or more centuries ago among Christiantheologians. Throughout the book, Griffin puts forward many original andinsightful ways of looking at Western thought, Christian theology, and therise of modernism. These insights deserve to be explored; they certainly shouldstimulate fruitful discussion.The major problem of Griffin's work for the Muslim is his desire, andthat of process theologians as a whole, to create a new religion. Huston Smithaddresses this issue in a forthcoming work where the two debate this andother issues. (I look forward to reading this book.) Griffin is not sufficientlyaware of the perennial perspective, which makes me predict that Huston Smithwill offer quite persuasive arguments against process theology. This perspectiveholds that no meaningful religious experience can take place without agrounding and foundation in a divinely revealed tradition. Islam has beencompleted and protected by Allah Himself in the form of the Qur'an andthe Sunnah, and so we need not create a new religion to appreciatepremodernity or to destroy modernity. It is the task of Islamic scholars toengage the issues Griffin brings up, a project which will surely lead us torediscover ideas and processes in our heritage which may be fruitfully ...